2003
DOI: 10.1177/112067210301300407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ibopamine Eye Drops on Intraocular Pressure and Aqueous Humor Flow in Healthy Volunteers and Patients with Open-Angle Glaucoma

Abstract: The results seem to confirm that ibopamine increases aqueous humor production in normal and glaucomatous eyes, raising IOP only in eyes with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
8
0
6
Order By: Relevance
“…22 Previous studies have demonstrated that ibopamine eye drops can cause an IOP increase in subjects having a reduced functioning of the outflow structures, which include patients with: POAG, normal tension glaucoma, positive family history, and hydrodynamic disorders caused by corticosteroids; healthy patients, on the other hand, tend to show no influence on IOP with ibopamine. 23,24 The ibopamine test has been reported to be an efficient provocative test in the management of glaucoma and patients at risk. 25 The purpose of this study was to determine whether higher IOP values, lower CCT measurements, positive ibopamine test results, SAP, SWAP, FDT, CSLO, or SLP alterations at baseline might be associated with an increased risk for development of POAG in OHT patients.…”
Section: Introductionmentioning
confidence: 99%
“…22 Previous studies have demonstrated that ibopamine eye drops can cause an IOP increase in subjects having a reduced functioning of the outflow structures, which include patients with: POAG, normal tension glaucoma, positive family history, and hydrodynamic disorders caused by corticosteroids; healthy patients, on the other hand, tend to show no influence on IOP with ibopamine. 23,24 The ibopamine test has been reported to be an efficient provocative test in the management of glaucoma and patients at risk. 25 The purpose of this study was to determine whether higher IOP values, lower CCT measurements, positive ibopamine test results, SAP, SWAP, FDT, CSLO, or SLP alterations at baseline might be associated with an increased risk for development of POAG in OHT patients.…”
Section: Introductionmentioning
confidence: 99%
“…A ibopamina é uma pró-droga da N-metildopamina, hidrolisada em epinina, com atividade nos receptores adrenérgicos e dopaminérgicos (3) . Apresenta uma ação midriática não-cicloplégica (4) devido a suas propriedades alfa-adrenérgicas (5) , e é capaz de induzir a um aumento transitório da pressão intraocular (PIO) por aumentar a produção de humor aquoso através de sua ação nos receptores D1 dopaminérgicos (6)(7)(8) .…”
Section: Resumo Introduçãounclassified
“…O mesmo teste em olhos normais não foi capaz de elevar a PIO a níveis estatisticamente significativos (3,5) , levando a uma boa relação sensibilidade/especificidade na diferenciação entre olhos normais e glaucomatosos (10)(11)(12)(13)(14) .…”
Section: Resumo Introduçãounclassified
“…Der mydriatische Effekt von Ipopamin Chlorhydrat 2 % ist größer im Vergleich zu Phenylephrin 10 % oder Tropicamid 1 % [10]. Als Nebeneffekt der Mydriase wurde eine, zum Teil erhebliche, Steigerung der Kammerwasserproduktion beobachtet, die zunehmend eine selbstständige Anwendung in der Ophthalmologie findet [2,4,11,16]. Dieser Effekt beruht vorwiegend auf der Aktivierung der alpha-adrenergen (a1, a2) neben den beta-adrenergen (ß1, ß2) Rezeptoren im Ziliarkörper [10].…”
Section: Introductionunclassified
“…Die 2-%-Ibopamin-Augentropfen können entsprechend a) als Mydriatikum und b) als Provokationstest beim Offenwinkelglaukom eingesetzt werden: Im Unterschied zu gesunden Augen, die keine nennenswerte Veränderung des Intraokulardruckes (IOD) nach einmaliger Applikation zeigen, steigt der IOD in Glaukomaugen 45 -60 Minuten nach der Tropfenapplikation um 3,2 -8 mmHg; der Effekt ist kurzfristig und reversibel [2,4]. Im weiteren gibt es Fallberichte über die Behandlung von okulärer Hypotonie in Kombination mit topischen Corticosteroiden [1,14].…”
Section: Introductionunclassified